Learning from perpetrator replacement to remove crime opportunities and prevent poaching of the Sundarbans tiger - Nasir Uddin; Sam Enoch; Abishek Harihar; Rob S. A. Pickles; Tasnim Ara; Alice C. Hughes (Conservation Biology, 2023)
Illegal wildlife trade (IWT) is one of the leading causes of the decline in high‐value species. Crime‐reduction strategies to counter IWT can have unintended effects, with crime displacement occurring when offenders react to such interventions. Despite the value of understanding how and why displacement occurs for informing conservation strategies, few examples are published. We explored a case of perpetrator replacement following an intervention and drew lessons for conservation strategies for high‐value species. Poaching and subsequent trade threaten the Sundarbans tiger ( Panthera tigris ). Pirate gangs were the dominant poachers from 1980 to 2017, but following an extensive campaign, the Sundarbans was declared pirate free in 2018. We interviewed 280 individuals, including 100 tiger poachers, from 26 administrative unions bordering the Sundarbans and used interviewee responses to compare the poaching situation during and after the pirate era. We analyzed the spatial distribution of tiger poachers among the unions and used crime script analysis of the dominant poacher type to identify intervention. Because pirates opportunistically poached tigers, the government's successful counter‐pirate campaign inadvertently removed the dominant tiger poaching type. However, a temporary reduction in poaching was rapidly cancelled out by the emergence of at least 32 specialist tiger‐poaching teams. With the risk of extortion and robbery from pirates gone, other groups increased the frequency of opportunistic and targeted tiger poaching. Based on expert interviews, we estimated that 341 tiger poachers of all types are active throughout the unions, with 79% of specialists concentrated in 27% of unions. The highly focused counter‐pirate campaign reduced motivations and opportunities for piracy but left intact the opportunity structure and trade connections for tiger poaching, and with insufficient enforcement officers trading has flourished. Interventions targeting opportunities for poaching by specialist tiger poachers include heightened surveillance and reporting mechanisms and alternative livelihood provision to disincentivize poaching.

An investigation into the future changes in rainfall onset, cessation and length of rainy season in the Oti River Basin, West Africa - Daniel Kwawuvi; Daouda Mama; Sampson K. Agodzo; Andreas Hartmann; Isaac Larbi; Enoch Bessah; Tesfalem Abraham; Sam-Quarcoo Dotse; Andrew Manoba Limantol (Modeling Earth Systems and Environment, 2022)